Peran Keluarga dalam Meningkatkan Kesehatan Mental Pasien Hipertensi - Enni Juliani; Rizqa Wahdini; Felicia Risca Ryandini; Yarwin Yari; Arlies Zenitha Victoria (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Hypertension is a non-communicable disease requiring long-term management and is often accompanied by psychological problems such as stress and anxiety. Poor mental health can affect treatment adherence and reduce patients’ quality of life. Family plays a vital role as the primary support system in helping individuals adapt to chronic conditions. This community service activity aimed to strengthen the role of family in supporting the mental health of patients with hypertension. The program was conducted in Plombokan Subdistrict, Semarang City, on November 26–27, 2025, involving 45 participants, including patients and their family members aged from middle adulthood to pre-elderly. Methods used were health education, interactive discussions, and family counseling. Evaluation was conducted descriptively by measuring family knowledge and patients’ mental health before and after the intervention. Results showed increased family knowledge and awareness, along with reduced mild stress and anxiety among patients. A family-based approach is effective as a promotive and preventive community strategy.